ANALISIS KINERJA ALGORITMA RSA PADA ENKRIPSI CITRA DIGITAL BERDASARKAN PARAMETER PSNR DAN MSE - Jamaluddin; Darwis Robinson Manalu; Paska Marto Hasugian; Roni Jhonson Simamora (Universitas Methodist Indonesia, 2026)
Digital image security is an important issue in this era of increasingly massive multimedia-based data exchange, especially for sensitive information that requires a high level of protection. This study aims to analyze the performance of the Rivest Shamir Adleman (RSA) asymmetric cryptography algorithm in the digital image encryption process based on the Mean Squared Error (MSE) and Peak Signal-to-Noise Ratio (PSNR) parameters, as well as encryption and decryption times. The method used is a quantitative experiment on 30 digital images with varying resolutions (256×256, 512×512, and 1024×1024 pixels) and two RSA key lengths (1024-bit and 2048-bit). The test results show that the MSE value ranges from 0.001068 to 0.002620 and the PSNR value ranges from 75.08 to 78.34 dB, indicating that the decrypted images are of very high quality and close to the original images. However, the computation time increased significantly with increasing resolution and key length, with RSA 2048-bit taking almost twice as long as RSA 1024-bit. These findings show that the RSA algorithm is very effective in maintaining the integrity of digital images, but has limitations in terms of computational time efficiency, especially for high-resolution images. Therefore, a balance between security and performance is needed in practical implementation.